2019
DOI: 10.1111/pce.13659
|View full text |Cite
|
Sign up to set email alerts
|

Soil strength influences wheat root interactions with soil macropores

Abstract: Deep rooting is critical for access to water and nutrients found in subsoil. However, damage to soil structure and the natural increase in soil strength with depth, often impedes root penetration. Evidence suggests that roots use macropores (soil cavities greater than 75 μm) to bypass strong soil layers. If roots have to exploit structures, a key trait conferring deep rooting will be the ability to locate existing pore networks; a trait called trematotropism. In this study, artificial macropores were created i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…The pores in the cores are not only hydrologically important for providing quick pathways for fluid to flow through, they are also biologically critical for modulating nutrient cycling as well as root growth ( Atkinson et al, 2020 ). An increase in porosity and permeability of the cores could lead to a rise in yield due to the increase in nitrification and root penetration as our previous work based on the Rothamsted long-term experiments showed that more porous and permeable soils were positively related to abundance of nitrification-related genes ( Neal et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…The pores in the cores are not only hydrologically important for providing quick pathways for fluid to flow through, they are also biologically critical for modulating nutrient cycling as well as root growth ( Atkinson et al, 2020 ). An increase in porosity and permeability of the cores could lead to a rise in yield due to the increase in nitrification and root penetration as our previous work based on the Rothamsted long-term experiments showed that more porous and permeable soils were positively related to abundance of nitrification-related genes ( Neal et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that, in this study, the subsoil roots of spring barley colonized the biopores due to a hard setting soil environment. As Atkinson et al [50] have reported, colonization of macropores is an important strategy of wheat roots to compacted subsoil. Contrary to homorhizous barley, allorhizous faba bean, with its thicker roots [51], less plasticity [52], and independance from nitrogen in the sheath, might be less attracted by the biopore sheath.…”
Section: Discussionmentioning
confidence: 95%
“…The biopores not only provided paths with lower mechanical resistance, but also altered the physical, chemical, and biological properties of the surrounding soil that benefit root growth ( Kautz et al , 2013 ; Banfield et al , 2017 ). In previous studies, artificial pores have been created to study root behaviour in soil ( Pfeifer et al , 2014 ; Colombi et al , 2017 ; Atkinson et al , 2020 ). In these examples, the soil was artificially packed; the soil around artificial pores is most likely to have similar chemical properties to the bulk soil.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fradgley et al (2020) demonstrated significant differences in the near-surface architecture of wheat roots on a selection of modern and historic wheat lines, but whether this translates into differences in deep rooting remains to be determined. It is likely that where biopores are not immediately accessible, roots undertake foraging-like behaviour in order to secure an easier passage through the soil ( Atkinson et al , 2020 ). Roué et al (2020) recently demonstrated, for Arabidopsis, that the root cap size and shape can influence the penetration ability of roots; however, by the resolution adopted in our imaging approach, it was not possible to accurately measure root caps to assess this and therefore is suited to future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation